Sustaining Protein Nutrition Through Plant-Based Foods - Langyan, Sapna; Yadava, Pranjal; Khan, Fatima Nazish; Dar, Zahoor A.; Singh, Renu; Kumar, Ashok (Frontiers in Nutrition, 2022)
Proteins are essential components of the human diet. Dietary proteins could be derived from animals and plants. Animal protein, though higher in demand, is generally considered less environmentally sustainable. Therefore, a gradual transition from animal to plant-based protein food may be desirable to maintain environmental stability, ethical reasons, food affordability, greater food safety, fulfilling higher consumer demand, and combating protein-energy malnutrition. Due to these reasons, plant-based proteins are steadily gaining popularity, and this upward trend is expected to continue for the next few decades. Plant proteins are a good source of many essential amino acids, vital macronutrients and are sufficient to achieve complete protein nutrition. The present review comprehensively explores the nutritional quality of the plant proteins, their cost-effective extraction and processing technologies, impacts on nutrition, different food wastes as an alternative source of plant protein, and their environmental impact. Further, it focused on the emerging technologies for improving plant proteins' bioavailability, digestibility, and organoleptic properties and highlighted the aforementioned technological challenges for future research work.